THE INFLUENCE OF IMAGE CONSULTING ON EXECUTIVE PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Luiz Cerbasi de Almeida, André (Revista Gênero e Interdisciplinaridade, 2026)
This systematic literature review analyzes the influence of image consulting on executive performance. The management of appearance and non-verbal communication has become a strategic component for professional success, impacting the perception of competence, leadership, and trustworthiness. Through a systematic search in databases such as PubMed, Scopus, Web of Science, EBSCO, and Google Scholar, 17 empirical studies published between 2019 and 2024 that investigate the relationship between personal image and executive performance indicators were selected. The results indicate that a well-managed professional image is positively associated with better business outcomes, such as closing sales and attracting investments, in addition to strengthening self-confidence and leadership presence. The analysis of the literature reveals that psychological mechanisms such as enclothed cognition and the halo effect play a fundamental role in how appearance influences self-perception and the perception of others. It is concluded that image consulting is a high-impact executive development intervention, although there are gaps in the literature on measuring its return on investment and its application in different cultural contexts. Directions for future research are proposed, with emphasis on longitudinal, cross-cultural studies with greater sample diversity.